Analisis Pengaruh Citra Merek, Inovasi Produk Dan Iklan Terhadap Kinerja Pemasaran Melalui Keunggulan Bersaing Sebagai Intervening - Dita Dewi Ramadzan (PRAGMATIS, 2020)
In the current era of globalization, developments in the field of technology are increasingly sophisticated. Smartphones are difficult to separate from activities carried out by humans everyday, there is internet support that makes it easier for humans to connect with anything around the world, social media that makes humans able to communicate with each other over great distances even without meetings.The purpose of this study was to examine and analyze the influence of brand image, product innovation and advertising on the marketing performance of "OPPO" smartphones on students of the Faculty of Economics and Business at Wijaya Kusuma University in Surabaya through competitive advantage as an intervening variable. The population in this study is the Students of the Faculty of Economics and Business, University of Wijaya Kusuma Surabaya who use smartphones "OPPO". The number of samples taken was as many as 100 respondents taken using random sampling techniques in which each element of the entire population had the same opportunity to be chosen. Path analysis is used as a calculation to test the hypothesis in this study.From the research that has been done, it can be seen that brand image, product innovation and advertising do not have a significant influence on the competitive advantage of "OPPO" smartphones in the students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. Competitive advantage has a significant effect on the marketing performance of "OPPO" smartphones in the students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. Brand image, product innovation and advertising do not have a significant effect on the marketing performance of the "OPPO" smartphone on the students of the Faculty of Economics and Business, University of Wijaya Kusuma Surabaya. And competitive advantage is not tested as an intervening variable because the direct influence of brand image, product innovation and advertising on marketing performance is greater than the indirect effect.